Antioxidant and Antimicrobial Properties of Tamarindus indica L. - Bibekananda Meher; Deepak Das (International Journal of Phytomedicine, 2013)
In this study, in vitro antioxidant and antimicrobial activities of aqueous and Hydroalcoholic extracts of leaves Tamarindus indica were investigated. In-vitro antioxidant assay was performed by DPPH (1, 1 –diphenyl-2-picrylhydrazyl) assay, Hydroxyl radicals scavenging assay, Ferric reducing assay, Nitric oxide radical scavenging assay. Percentage of free radical scavenging potential was determined using ascorbic acid as a standard in each method. In Ferric reducing antioxidant power assay, antioxidant power was determined by measuring ferric reducing values. It was observed that hydroalcoholic extracts were having more potential antioxidants. Hydroalcoholic extract at 500 µg/ml shown maximum FRAP value 0.76±0.08. IC50 values were determined for each extracts. Lowest IC 50 value was exhibited by HAETIS in DPPH, Hydroxyl radical scavenging, Ferric reducing and NO scavenging methods are: 195.30µg/ml,182.02µg/ml,196.23µg/ml respectively. These results indicated that the anti oxidant capacities depends on concentration and nature of extracts. Antimicrobial activities were evaluated by determining inhibition zone diameter and calculated MIC values. Aqueous extracts of Tamarindus indica leaves shown maximum inhibition zone diameter against gram positive bacteria Staphylococcus aureus 17.33±1.5 mm and was exhibited by Ciprofloxacin used as standard 36.0±2.0mm. In gram negative bacteria Pseudomonas aeruginosa hydroalcoholic extracts of Tamarindus indica leaves shown 24.66±.51mm and Gentamicin used as standard 37.0±1.73. Aqueous extracts of leaves shown good antimicrobial activity against gram positive bacteria and hydroalcoholic extracts of leaves in gram negative bacteria. Minimum inhibitory concentration shown by different extracts were in the range of 8-20mg/ml. Hydroalcoholic extracts of leaves shown lowest minimum Inhibitory concentration 8mg/ml against Pseudomonas aeruginosa.